Textpattern Solutions: PHP-Based Content Management Made Easy - Potts, Kevin; Sable, Robert; Smith, Nathan; Fredborg, Mary.; Lindley, Cody.; SpringerLink (Online service) (Berkeley, CA : Apress, 2007)
Textpattern is a powerful, PHP-based content management system that allows you to build pretty much any kind of data-driven website quickly and easily. It is very popular among designers and developers alike, and has an active community of users. Sound good? Well, you're in luck$1 (Bthis book shows you how to use every aspect of Textpattern to a professional standard. Textpattern (and this book) appeals to two main groups of people: Firstly, the web designer who has mastered the fundamentals of XHTML and CSS and wants to create sites that have fresh and dynamically changing information, but is not familiar with server-side coding and databases. Never fear$1 (BTextpattern enables you to integrate your XHTML knowledge, inserting dynamic aspects into your already solid site design. Secondly, PHP developers who are looking for a content management system upon which to build additional functionality and want a hand with the design aspects of their site. Again, Textpattern fills in those holes. The book leaves no stone unturned. It starts by introducing you to Textpattern and guiding you through its very simple installation process. After the core features of the administrative interface are explored, the book dives into building sites with TXP, using CSS, articles, forms, pages, and more to create fully customized templates. Development follows next, looking at installing plugins and building your own custom plugins to further enhance your Textpattern-based site. The book concludes with several case studies to provide ideas and inspiration, including a weblog, an e-commerce site, and an online review directory.s
Getting started -- Setting the Stage -- Installing Textpattern -- The Textpattern Interface -- Site Administration -- Basic Content Manipulation -- Presentation -- Customizing Textpattern -- The Textpattern Model -- Creating The Content:Categories and Articles -- Customizing The Presentation: Sections, Pages, Forms, and Style -- Tying Content and Structure Together -- Comments -- Beyond The Basics -- Extending Textpattern -- Custom Fields -- Using Plugins -- Writing Plugins -- Textpattern Site Examples -- Multiauthor Weblog -- Case Study: Popularweddingfavors.Com -- Case Study: Boisecityeats.Com.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books